Mapping our selves : Canadian women's autobiography in English - Buss, Helen M. (McGill-Queen's University Press, 1993)
In Mapping Our Selves Helen Buss considers a broad range of autobiographical works written by Canadian women, including memoirs, journals, and conventional autobiography as well as experiments in blending a number of writing genres. She constructs her own "mapping" theory of how female identity is formed in order to illustrate how identity can be understood through the relationship between writer, text, and reader. Buss supplies a framework for her study by reviewing male-centred theories of identity and some of the ways in which theorists working with women's autobiographical accounts are changing these models. The texts selected by Buss include those by Elizabeth Simcoe, Susanna Moodie, Anna Jameson, Nellie McClung, Lucy Maud Montgomery, Emily Carr, Laura Salverson, Margaret Laurence, Dorothy Livesay, Daphne Marlatt, Mary Meigs, Maria Campbell, Kristjana Gunnars, and Aritha van Herk. Each section of the book opens with a short autobiographical introduction by Buss, allowing the reader to place the author's critical practice within the context of her sense of her own identity as critic, writer, and woman.-- publisher